Legislation and quality of nursing education in the context of the COVID-19 pandemic - Josicélia Dumêt Fernandes; Ana Lúcia Arcanjo Oliveira Cordeiro; Giselle Alves da Silva Teixeira; Rosana Maria Oliveira Silva; Gilberto Tadeu Reis da Silva (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to reflect on the governmental normative acts issued for higher education during the COVID-19 pandemic and on the repercussions of these acts on the quality of nursing education in Brazil. Methods: this is a reflection on the repercussions for the quality of nursing education, based on the normative acts applied to higher education, enacted from March to December 2020, available on the Ministry of Education website and in the current literature on the subject anchored in the National Curriculum Guidelines for the Undergraduate Nursing Course. Results: educational legislation, in the context of the pandemic, distanced education from the world of work, as well as from the quality of training established in the guidelines. Final Considerations: remote teaching in nursing makes it difficult to train professionals with the capacity to effectively teach and learn in the real world of care and health promotion in the Unified Health System.